Relevansi Moderasi Islam terhadap Toleransi Antarumat Beragama dalam Masyarakat Multikultural Indonesia - Siti Nurrahmatin Ni’mah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article aims to examine the importance of Islamic moderation in fostering interreligious tolerance in Indonesia, a country characterized by cultural, ethnic, and religious diversity. Islamic moderation, or Islam wasathiyyah, is understood as a religious attitude that emphasizes justice, balance, and tolerance in social life. This study employs a library research method by reviewing various sources such as books, academic journals, and official documents related to religious moderation, tolerance, and Indonesia’s multicultural society. This approach is intended to gain a comprehensive understanding of the concept of Islamic moderation and its application in socio-religious life. The findings indicate that Islamic moderation plays a strategic role in reducing extremist attitudes, preventing religion-based conflicts, and strengthening social harmony amid Indonesia’s diverse society. Furthermore, Islamic moderation functions as a bridge between religious teachings and social realities by balancing the vertical relationship between humans and God and the horizontal relationship among fellow human beings. The implementation of Islamic moderation through education, interfaith dialogue, social cooperation, and public policy support has proven to be relevant in strengthening interreligious tolerance. Therefore, Islamic moderation is not only a theological demand but also a social and national necessity in maintaining unity, peace, and the integrity of the Indonesian nation. Keywords: Islamic Moderation, Multicultural Society, Religious Tolerance